2012
DOI: 10.3892/br.2012.36
|View full text |Cite
|
Sign up to set email alerts
|

Fixed rate of blood component improves the survival rate of patients in massive transfusion

Abstract: Abstract. The aim of this study was to examine the manner in which varying proportions of serum and red blood cells (RBC) in massive blood transfusion affect the survival rates of patients with severe blood loss. Massive transfusion (MT) was determined as receiving ≥10 units of red blood cells in 24 h. The electronic medical records and blood transfusion information for the period January, 2002 to December, 2011 of patients with MT were examined. Moreover, we calculated the ratio of blood components and examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The main body of evidence is from retrospective data in massive transfusion, where civilian and military trauma studies showed a survival benefit in patients who received higher FFP:red cells ratio (so called 1:1 ratio) [40][41][42][43]. However, this data have been criticised in that there was survivorship bias because patients who died on arrival at the emergency centre would not have had time to receive FFP.…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%
“…The main body of evidence is from retrospective data in massive transfusion, where civilian and military trauma studies showed a survival benefit in patients who received higher FFP:red cells ratio (so called 1:1 ratio) [40][41][42][43]. However, this data have been criticised in that there was survivorship bias because patients who died on arrival at the emergency centre would not have had time to receive FFP.…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%